The effect on land-use changes on water availability in the Cidongkol Irrigation Area. Issue 2 (March 2021) - Permana, S; Zhafirah, A; Johari, G J; Purnamasari, I; Farida, I
Abstract: The city of Tasikmalaya has now changed, especially in the field of infrastructure. The impact of infrastructure development affects uncontrolled land-use change. One of the transportation infrastructure built by the City of Tasikmalaya Government is Mangin Road. Paddy fields that meet the area gradually began to become settlements. Transfer of land functions in the area, resulting in reduced paddy fields. The Cidongkol Irrigation Area currently has a 116 ha rice field area from an initial 192 ha area. The purpose of this study was to determine the fulfilment of the rice field area and to be associated with previous research. The data processing method is analyzing the availability that comes from Cikalang Channel and water needs. In the initial condition, the required discharge of about 92% was not fulfilled. Whereas with an area of 116 ha of rice fields, around 92% was not met. Cikalang Channel serves 246 ha of paddy fields. With conditions like this, Cikalang Channel is not able to serve the entire area. To meet water needs, farmers use modified cropping patterns. The City Government of Tasikmalaya has managed the excavation area, and part of the land has been replanted to restore its function.